No Mere Shadows : Faces of Widowhood in Early Colonial Mexico - Flint, Shirley Cushing; Flint, Shirley Cushing (Book collections on Project MUSE., 2013)
"Shirley Flint explores the stories of three widows in Mexico City, giving us a glimpse at the structure of everyday life in colonial Mexico, especially the ways that women conducted business, practiced religion, and manipulated politics. Each of these widows' stories illustrates an often overlooked aspect of Spanish life in the New World"--Provided by publisher.